2007
DOI: 10.1258/095646207780132497
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenon of missing doses in a cohort of HIV patients with good adherence to highly active antiretroviral therapy

Abstract: A self-administered questionnaire survey was conducted in a specialist HIV clinical service in Hong Kong. A total of 76 male Chinese patients who had been on highly active antiretroviral therapy for over one year were enrolled. All except one had undetectable viral load at the time of the assessment. Though a majority (76%) scored 100% in self-reporting adherence rating, one-third of these had in fact missed at least one dose in the preceding four-week period. Men having sex with men had a lower tendency of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For the 36 studies included here, there were no disagreements between the first reviewer (LL) and the second reviewer (ZM). Fig 1 shows the flowchart for selecting articles [ 6 – 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the 36 studies included here, there were no disagreements between the first reviewer (LL) and the second reviewer (ZM). Fig 1 shows the flowchart for selecting articles [ 6 – 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nonadherence is a dynamic process; it varies over time, and may be expressed in different forms, such as a ‘missed dose phenomenon’ [11,12] or the interruption of therapy. Many studies on adherence in HIV‐infected patients have focused on quantitative and global measures, and only a few studies have reported data beyond 3 years of follow‐up [13–15].…”
Section: Introductionmentioning
confidence: 99%